Critical Role of Transcript Cleavage in Arabidopsis RNA Polymerase II Transcriptional Elongation. Issue 5 (9th March 2020) - Antosz, Wojciech; Deforges, Jules; Begcy, Kevin; Bruckmann, Astrid; Poirier, Yves; Dresselhaus, Thomas; Grasser, Klaus D.
Abstract : Backtracking/arrest of RNA polymerase II commonly occurs during transcript elongation and reactivation of the enzyme is a prerequisite for plant growth. Abstract: Transcript elongation factors associate with elongating RNA polymerase II (RNAPII) to control the efficiency of mRNA synthesis and consequently modulate plant growth and development. Encountering obstacles during transcription such as nucleosomes or particular DNA sequences may cause backtracking and transcriptional arrest of RNAPII. The elongation factor TFIIS stimulates the intrinsic transcript cleavage activity of the polymerase, which is required for efficient rescue of backtracked/arrested RNAPII. A TFIIS mutant variant (TFIISmut) lacks the stimulatory activity to promote RNA cleavage, but instead efficiently inhibits unstimulated transcript cleavage by RNAPII. We could not recover viable Arabidopsis ( Arabidopsis thaliana ) tfIIs plants constitutively expressing TFIISmut. Induced, transient expression of TFIISmut in tfIIs plants provoked severe growth defects, transcriptomic changes and massive, transcription-related redistribution of elongating RNAPII within transcribed regions toward the transcriptional start site. The predominant site of RNAPII accumulation overlapped with the +1 nucleosome, suggesting that upon inhibition of RNA cleavage activity, RNAPII arrest prevalently occurs at this position. In the presence of TFIISmut, the amount of RNAPII was reduced, which could be reverted by inhibiting the proteasome, indicating proteasomal degradation of arrested RNAPII. Our findings suggest that polymerase backtracking/arrest frequently occurs in plant cells, and RNAPII-reactivation is essential for correct transcriptional output and proper growth/development.